Calidad fisiológica de semilla de maíz (Zea mays L.) y su efecto en la productividad en el Ecuador - Franco Vite, Luis Adrián (2023)
Seed serves as a raw material for agricultural production, so it is crucial that it responds well to the planting environment and encourages the growth of robust plants in order to perform at its best. The objective was to describe the physiological quality of corn seed (Zea mays L.) and its effect on productivity in Ecuador. The findings determine that seeds with lower physiological quality indices become less valuable, reducing production levels of a particular crop, which plays an important role in influencing production; Users of seeds sold in various agricultural centers assume that the seeds they buy will play their role in the production of the chosen species; farmers can obtain high yields from corn hybrids due to their high productivity potential; It is necessary to emphasize the importance of physiological analyzes of the seed because to obtain good production, good quality seeds are necessary with tests that ensure their quality and profitability. In this way, maintaining seed quality is of great help to increase crop productivity in a sustainable and sustainable manner; By expressing their behavior in vigor and viability when analyzing physiological verification tests, genotypes that exhibit physiological quality can be decisively distinguished through seed vigor tests, resistance tests and the accelerated aging method and the best corn seed according to its potential. Hybrids are productive, especially Pioneer 4039 with 10.90 tn/ha.